Music therapy in Special Education - Salamanca Herrero, Diego (Pulso. Revista de educación, 2003)
In Spain, music therapy is increasingly being used as a complementary therapy for people with mental, physical, and sensory disabilities, as well as patients with medical, neurological, and geriatric conditions, etc. This article explores examples of music being used as a therapeutic tool in various cultures and throughout history. It also examines different centres in the Autonomous Community of Madrid where music therapy is implemented, the methodologies used, and techniques employed. Additionally, practical experiences of music therapy in Special Education and a clinical case study are presented to conclude the article.